Reproductive dynamics of Lycengraulis grossidens (Clupeiformes: Engraulidae) and Platanichthys platana (Clupeiformes: Clupeidae) in a subtropical coastal lagoon - Lopes,C. A. (2018)
Abstract We evaluated the reproductive dynamics of two fish species, Lycengraulis grossidens and Platanichthys platana, in a subtropical freshwater coastal lagoon (Peri Lagoon) in Brazil. Samples were collected from nine sites every two months from June 2008 to April 2012. Different fishing methods were used to capture larvae, juveniles, and adults. Limnological variables were obtained using multiparameter probe. More females than males were collected of both fish species and the chi-square test (χ2) was used to confirm that the sex ratio was female-biased. Large numbers of maturing and mature fishes were observed in almost every sampling month. The gonadosomatic index (GSI) of L. grossidens was the highest in August, October, and December for females and in October for males, and no significant difference was found across years. The GSI of P. platana showed no significant difference across months for either sex; however, significant differences were recorded in year three (June 2010-April 2011) and year four (June 2011-April 2012) for females and in year three (June 2010-April 2011) for males. For both species, GSI was negatively correlated with temperature and water level. L. grossidens larvae were more abundant in October 2010, showing a positive correlation with water transparency, whereas P. platana larvae were more abundant in June 2011, showing a positive correlation with water transparency and negative correlation with temperature and precipitation. Both species were represented by different stages, including larvae, which confirm that these species reproduce in Peri Lagoon. Reproduction was more pronounced in autumn and winter; however, reproductive activity was evident throughout the sampling period. In conclusion, our results show that abiotic factors strongly influence the temporal pattern of reproductive activity and larval assemblages of both L. grossidens and P. platana in Peri Lagoon, Brazil.